Unlocking Nigerian Universities’ Role in Poverty Reduction: Challenges, Opportunities, and Pathways to Sustainable Development - Sulaiman, Musa Mohmmed; Bello, Ganiyu; Alabi, Hafsat Imam; Imam, Bashirat Titilope; Bello, Zakariyau Adebayo; Ahmed, Aduke Rihanat (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
Reducing poverty and achieving sustainable development are critical goals for Nigeria. Universities, as hubs of advanced learning, possess the capacity to generate the knowledge, skills, and innovations necessary to tackle the fundamental issues contributing to poverty. However, for universities to fully harness this potential, they must address several challenges, including inadequate funding, insufficient equipment, and subpar teaching quality. This paper explores the role of Nigerian universities in poverty alleviation, as well as the challenges and benefits of their involvement. The discussion focuses on the concept of poverty, its prevalence both globally and specifically in Nigeria, a review of existing literature on poverty reduction strategies in Nigeria, and the primary causes of poverty in the country. Additionally, the paper highlights various barriers and opportunities for universities to enhance their contributions to poverty reduction in Nigeria. It advocates for the creation of a conducive environment for teaching, learning, and research within Nigerian universities and calls for stronger collaborations between academia and industry to promote entrepreneurship and innovation, ultimately supporting the achievement of Sustainable Development Goal 1.